Laparoscopic cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for limited peritoneal metastasis. The PSOGI international collaborative registry. Issue 6 (June 2021) - Arjona-Sanchez, A.; Aziz, O.; Passot, G.; Salti, G.; Esquivel, J.; Van der Speeten, K.; Piso, P.; Nedelcut, D.-S.; Sommariva, A.; Yonemura, Y.; Turaga, K.; Selvasekar, C.R.; et al.
Abstract: Introduction: A laparoscopic approach for cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (L-CRS+HIPEC) in highly selected patients has been reported in small cohorts with a demonstrable reduction in length of stay and post-operative morbidity. This study aims to analyse individual patient data from these international centres collected through the Peritoneal Surface Oncology Group International (PSOGI) L-CRS+HIPEC registry. Methods: An international registry was designed through a networking database (REDCAP®). All centres performing L-CRS+HIPEC were invited through PSOGI to submit data on their cases. Patient's characteristics, postoperative outcomes and survival were analysed. Results: Ten international centres contributed a total of 143 L-CRS+HIPEC patients during the study period. The most frequent indication was low grade pseudomyxoma peritonei in 79/143 (55%). Other indications were benign multicyst mesothelioma in 21/143(14%) and peritoneal metastasis from colon carcinoma in 18/143 (12, 5%) and ovarian carcinoma in 13/143 (9%). The median PCI was 3 (2-5). The median length of stay was 6 (5-10) days, with 30-day major morbidity rate of 8.3% and 30-day mortality rate of 0.7%. At a median follow-up of 37 (16-64) months 126/143 patients (88.2%) were free of disease. Conclusions: Analysis of these data demonstrates that L-CRS+HIPEC is a safe and feasible procedure in highly selected patients with limited peritoneal disease when performed at experienced centres. While short to midterm outcomes are encouraging in patients with less invasive histology, longer follow up is required before recommending it for patients with more aggressive cancers with peritoneal dissemination.